Peranan Roh Kudus dalam Mengajar - Tulle, Ferry Yeferson Tulle; Anita Mariana Parulian Butar-Butar; Chanita Christie; Juanda Yulianus; Kezia Verena (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2024)
The process of learning God’s words is also believed as a supranatural process. Factor of Holy Spirit is believed controlling all fields of ministry including education ministry. It has been a lot of questions turns out about how much the role of Holy Spirit in Christian education, especially in learning. Principally, Holy Spirit works in the life and ministry of the believers. Christian spiritual growth is the work of Holy Spirit starting from the process of new birth, by Holy Spirit. The inhabiting by Holy Spirit and the process of the fullfilment by the Holy Spirit are the works of Holy Spirit. Any Christian ministry is also activities done under the guidance and power of Holy Spirit. Holy Spirit has a strong correlation with the teaching of Christian Education (PAK). The existence and the role of Holy Spirit in PAK is the distinctive type of teaching, different with seculer teaching. Anyway. The role of Holy Spirit that is representation of Christ in Christian education is as a Great Teacher. Process of learning in Christian education is handled as a team by Holy Spirit and PAK teachers. Both of students and the teacher must together rely upon the guidance of Holy Spirit. The role of the Holy Spirit is also stated in the grace that He gives to advance the capacity of both teacher and studets. Some dimensions should be developed by the logical sense of both sides. But in spiritual dimension, Holy Spirit must become the only Person that is allowed to fill and and five reinforcement. Christian education is an education that is empowered by Holy Spirit.